Experimental Study on the Pore Structure of Middle- and Low-Rank Coal and Its Influence on Methane Adsorption - Gaini Jia; Ming Yang; Xuebo Zhang; Lei Liu (Geofluids)
The pore characteristics of coal have an important influence on the coal adsorption of methane. The liquid nitrogen adsorption method was used to study the pore structure of low- and middle-rank coal samples from two aspects: pore specific surface area and pore shape. Low-field nuclear magnetic resonance (NMR) technology was used to study the difference in methane adsorption of coal samples under the same adsorption conditions. The influence and mechanism of the pore structure of middle- and low-rank coal samples on gas adsorption are discussed and analyzed. The results show the following: (1) There are differences in the adsorption capacity of medium- and low-rank coal samples. Within 1 h of methane inflation, the methane adsorption capacity of middle-rank coals such as Henan Pingdingshan (PDS) and Shanxi Wangzhuang (WZ) and Xinjiang low-rank coals (XJ) increases by 36.4%, 31.7%, and 35.8%, respectively, and as the inflation time is extended to the cumulative inflation of 10 h, the order of the increase in methane adsorption capacity is still PDS>XJ>WZ. (2) The pore types of the experimental coal samples are mostly wedge-shaped pores and ink bottle-shaped pores. The order of the BET specific surface area of the coal samples is in the order of WZ>PDS> XJ, which means that the WZ samples can provide more adsorption sites for gas molecule adsorption, but under the same adsorption conditions, the WZ sample has the least amount of gas adsorbed. Further analysis shows that the order of the tortuosity of the coal sample is WZ>XJ>PDS, which means that the WZ sample has a large pore tortuosity, a long channel for methane molecules to diffuse into the internal pores of the coal sample, and large diffusion resistance. It is the main reason why the methane adsorption capacity of WZ coal samples is less than that of PDS and XJ coal samples in the same adsorption conditions.